Recent advances in network pharmacology applications in Chinese herbal medicine - Jian Hao (Traditional Medicine Research, 2018)
Network pharmacology is a new discipline based on the theory of systems biology and network analysis of biological systems to design the drugs. It comprehensively observes the intervention and influence of drugs on the disease network, and reveals the mystery of multi-molecular drugs synergistically acting on disease. These concepts reflect the ideas of multi-component, multi-target and system regulation, and have many similarities with the research ideas of traditional Chinese medicine, which focuses on syndrome differentiation and treatment, emphasizes the overall understanding of the etiology and pathogenesis. Network pharmacology can be used to predict and identify the target and active component of traditional herbal medicine, to clarify the mechanism of action, to scientifically explain the rules of the prescription, to explore the rules of real-world prescription, to discover new indications and new active compounds, and to study drug relocation, etc. The applications of network pharmacology in traditional herbal medicine were systematically summarized to demonstrate the significant value in these areas.